The effect of isolation on athletes` mental health during the COVID-19 pandemic - Senisik, S.; Denerel, N.; Köyagasioglu, Tunç, S. (The Physician and Sportsmedicine, 2021)
Objective: We aimed to explore whether the mental health status of professional athletes was affected by the isolation period in which organized sports were suspended due to the COVID-19 pandemic. Methods: A total of 612 volunteers between the ages of 18-38 enrolled in the study, 418 of them were athletes engaged in team sports or individual sports and 194 of them were non-athletes. Participants completed the Depression - Anxiety - Stress Scale 21 (DASS-21), the Impact of Events Scale-Revised (IES-R) and International Physical Activity Questionnaires (IPAQ). Non-parametric methods were used for comparisons between groups. The presence of a linear relationship was tested with the Spearman Correlation Test. A value of p<0.05 was accepted statistically significant. Results: A total of 571 participants, 372 males and 199 females, completed the study. Depression and anxiety symptoms were lower in athletes compared to non-athletes (p<0.05). Depression, anxiety and stress symptoms were similar in team athletes and individual athletes (p=0.232, p=0.444, p=0.116; respectively). The post-traumatic stress symptoms were lower in male team athletes than female team athletes (p=0.020) and non-athletes (p<0.001). Depression, anxiety and stress symptoms were found to be similar in men and women (p>0.05). There was a negative correlation between physical activity level and mental health symptoms (p<0.05). Conclusion: The mental health status of athletes was better than non-athletes, and the positive effect of sport, which was done until the break due to the isolation period, on mental health continued. These findings show that physical activity may help to protect mental health.